PENGARUH PRICE DISCOUNT DAN IN-STORE DISPLAY TERHADAP IMPULSE BUYING PADA LABELLO STORE MEDAN - Desma Erica Maryati Manik; Erveni (Jurnal Manajemen Bisnis Eka Prasetya, 2020)
The purpose of this study is to determine the effect of Price Discount on Impulse Buying at Labello Store Medan, determine the effect of In-Store Display on Impulse Buying at Labello Store Medan, determine the effect of Price Discount and In-Store Display on Impulse Buying at Labello Store Medan. The research methodology used descriptive quantitative method, the unit of analysis in this study is Labello Store Medan and its observation unit are customers of Labello Store Medan as many as 980 respondents. The technique of determining the number of samples used in this study was the Slovin formula and amounted to 91 respondents. The research method used is by data collection techniques through library research and field research conducted systematically based on research objectives. The analytical method used to solve problems and prove hypothesis is descriptive analysis, regression analysis. The test results of the coefficient of determination (R2) indicate that 94.20% of the Impulse Buying variable is influenced by Price Discount and In-Store Display variables, while the remaining 5.80% is explained by the influence of other factors variables outside the model such as fashion involvement, positive emotion, store image and social media.